Physical properties of Quaternary sediments from the western South Korea Plateau, East Sea. (10th September 2022) - Kim, Gil Young; Park, Kiju; Lee, Gwang Soo; Kim, So-Ra; Hong, Seok-Hwi; Um, In-Kwon; Yu, Shin
Abstract: Sediment samples were collected with a piston sampler (114 samples) and a box core sampler (266 samples) during research cruises on the R/V Tamhae 2 of the Korea Institute of Geoscience and Mineral Resources (KIGAM) from 2015 to 2019, to examine the characteristics of seafloor sediments from the western South Korea Plateau of East Sea. The in situ velocity was measured at four sites using a seafloor acoustic probe developed by KIGAM (KISAP). The samples were analyzed for their physical properties and the resulting data were examined to gain insights into the distribution patterns of the sediments and how the physical properties varied by burial depth. The actual velocity of the seafloor sediments was investigated by comparing the velocities in the laboratory and in situ velocity measurements at four sites. Overall, the physical properties agree well with the expected characteristics of marine sediments but there is considerable variation in the mean grain sizes. The sediment distributions either increases or decreases gradually with depth, reflecting transport from topographically high areas (e.g., possible source and/or shelf areas). The relationships between the physical properties of samples from two transects, one east-west and the other south-north, are different, and reflect the presence of tephra with a low grain density at the specified depth intervals. The laboratory velocity is higher (approximately 20–40 m/s) than the in situ velocity measured by the KISAP because of differences in the temperature (approximately 22 °C) and pressure (∼100 atmospheric pressure). However, the corrected laboratory velocity agrees well with the in situ velocity. Inconsistencies in the data, such as the measurement frequency and condition of each system, measurement interval, and sediment grain size, are probably responsible for some of the variations in the physical property data.